PENINGKATAN HASIL BELAJAR SKI MELALUI MEDIA AUDIO VISUAL DI KELAS VI MI NW 2 KEMBANG KERANG - Burhanuddin (Lembaga Bale Literasi, 2023)
This research is Classroom Action Research (CAR) which was carried out on 15 students of MI NW 2 Kembang Kerang which consists of 6 women and 9 men. This study aims the SKI Learning Objectives Improvement on Sunan Maulana Malik Ibrahim material by using the audio-visual media. The result of learning shows that cycle 1 of learning objectives which obtained by students who achieve learning mastery individually as many as 7 people or 46.66% while 8 people or 53.33% have not reached completeness of study. The average result obtained by students is 69.80 which does not complete the KKM determined by MI NW 2 Kembang Kerang is 70 in SKI lessons. In cycle 2 the results of the final student test showed only 15 students achieved completeness individually, namely 100%. In accordance with the mastery of classical learning, Schools are declared complete when 80% of students complete individually. This shows that students in class VI MI NW 2 Kembang Kerang have been able to solve the questions given by the teacher to SKI lessons and show improvement Thus learning using audio media visuals can improve learning outcomes, activeness, and motivation, the material delivered by the teacher understandable, the responsibility of students towards the task is quite high, and helps students to be actively involved in learning activities.